SCIENTIFIC AND TECHNICAL SOLUTIONS FOR THE MAINTENANCE OF AGRICULTURAL MACHINERY IN UZBEKISTAN IN ACCORDANCE WITH MODERN REQUIREMENTS - Xudaykuliyev Rajabboy Ruzmatovich,Kupaysinova Khurshida Arabboy kizi, Valijonova Nodira Bozorboy kizi, (International Multidisciplinary Journal for Research & Development, 2025)
Research on scientific and technical solutions for the maintenance of agricultural machinery holds significant importance in the field of modern agrotechnology. In order to ensure the efficient performance and uninterrupted operation of agricultural machinery, modern methods, technologies, and tools for technical maintenance have been developed. These studies discuss scientific analyses aimed at servicing processes during the production phase of machinery, their repair, modernization, and preventive inspections, as well as the application of innovative technologies and automation. The objective is to effectively organize all technical maintenance processes during the production and operational phases of agricultural machinery, ensuring continuity and reliability in their usage. Furthermore, the research focuses on developing and implementing new, user-friendly, environmentally safe, and adaptable technical solutions suited to changing conditions.